The Relationship between Personality and Handball Coach-Athlete Intimacy - Prabowo, Indra; Pratama, Andi Kurniawan; Risyanto, Aris (Indonesian Journal of Sport Management, 2024)
This study aims to determine the relationship between personality types and intimacy of handball coach-athletes. The hypothesis proposed in this study is that there is a significant relationship between personality types and intimacy of handball coach-athletes in facing PON NTT and NTB. The subjects in this study were handball athletes representing West Java in the XXII PON NTT AND NTB totaling 28 people. Data collection using the Personality Type scale To categorize individuals in personality types, researchers used the Myers-Briggs Type Indicator (MBTI) measuring tool with a total of 60 question items and the coach-athlete intimacy scale using the Coach-Athlete Relationship Questionnaire (CART-Q) with a total of 11 questions. The approach to this research is quantitative descriptive. The relationship criteria are based on p value> 0.05 then Ho is accepted, Ha is rejected and if p value <0.05 then Ho is rejected, Ha is accepted. So it can be stated that there is a significant relationship between personality type and the intimacy of the West Java handball coach-athletes in facing the XXII NTT and NTB PON.